2016
DOI: 10.1016/j.neuron.2015.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomics of the Dopamine Pathway Enables Discovery of Rap1 Activation as a Reward Signal In Vivo

Abstract: Dopamine (DA) type 1 receptor (D1R) signaling in the striatum presumably regulates neuronal excitability and reward-related behaviors through PKA. However, whether and how D1Rs and PKA regulate neuronal excitability and behavior remain largely unknown. Here, we developed a phosphoproteomic analysis method to identify known and novel PKA substrates downstream of the D1R and obtained more than 100 candidate substrates, including Rap1 GEF (Rasgrp2). We found that PKA phosphorylation of Rasgrp2 activated its guani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
122
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(124 citation statements)
references
References 76 publications
2
122
0
Order By: Relevance
“…In addition to ERK1/2, PKA has also been shown to phosphorylate RasGRP2 at multiple sites [26,27,28]. However, these studies have produced conflicting results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to ERK1/2, PKA has also been shown to phosphorylate RasGRP2 at multiple sites [26,27,28]. However, these studies have produced conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies have produced conflicting results. In the original studies [26,27], phosphorylation by PKA resulted in the inhibition of RasGRP2 in HEK293T cells, while the most recent study showed PKA-mediated activation of RasGRP2 in Cos-7 cells [28]. It is difficult to reconcile these results and perhaps future studies using purified proteins will clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Using tissue punches taken from the PAG, we detected a rapid and significant increase in pERK1,2, but not pCREB, in response to systemic administration of a D1/5 receptor agonist. Examples of previous studies relevant to our study have shown that (1) activation of D1 receptors by SKF 81297 can increase pERK (Gangarossa et al, 2012; Gangarossa et al, 2013, (2) that the increase in pERK by SKF 81297 can be blocked by the D1 receptor antagonist SCH23390 (Gangarossa et al, 2011), and (3) that the SKF 81297-mediated increase in pERK is PKA-dependent (Florentini et al, 2011; Nagai et al, 2016). To be clear, ERK1,2 is believed to be activated indirectly by PKA through other mechanisms, including Ras/Raf/Rap or the cAMP-dependent, PKA-independent exchange protein Epac (Kawasaki et al, 1998; Gelinas et al, 2008).…”
Section: Dopamine Receptor Function/signal Transduction In the Pagmentioning
confidence: 62%
“…In order to construct pAAV‐syn‐tTA‐nls, tTA‐nls was subcloned into the BamHI and Hind III sites of pAAV‐syn‐GFP. AAV was prepared as described previously . AAV titers were estimated via a quantitative polymerase chain reaction.…”
Section: Methodsmentioning
confidence: 99%